The Stakes Could Not Be Higher: The Allied Response in Ukraine - Richard Arnold (Journal Of Global Strategic Studies, 2022)
Why are the United States and other western NATO allies so invested in the war in Ukraine? Why have NATO partners provided such enormous military assistance? This short essay argues that Russia’s attempt to override the sovereignty of its neighbour poses a threat not just to Ukraine (although it is, of course, principally that) but also a threat to the modern world order which is built on fundamentally liberal institutions. Nor is it just the fact of Russia’s invasion (второжение) but also how the war is being prosecuted. The essay then examines President Volodymyr Zelensky’s attempts to cultivate his image in line with Western heroes like Washington and Churchill before turning to rebutting potential criticisms. In all, the essay concludes that the stakes for the world could not be higher.